On the difference in swing arm kinematics between low handicap golfers and non-golfers using wireless inertial sensors - Lai, D. T. H.; Hechtl, M.; Wei, X. C.; Ball, K.; Mclaughlin, P. (Procedia Engineering, 2011)
The biomechanics of the golf swing has been an area of intense research interest in an attempt to improve swing performance and minimize golf related injuries e.g. lower back pain, golfer's elbow and tendon injuries. Measurements of golf swing kinematics have been previously done using optical motion capture systems e.g. Vicon, Optotrak, which require expensive bulky cameras and long setup times. Further, these systems have largely been limited to the lab or controlled outdoor environments. The recent introduction of micro-electromechanical systems (MEMs) inertial sensors has opened up new avenues to measuring human movement in sports during actual play and competition performance. These sensors have a small form factor, are lightweight, portable and cost effective. In this paper, we analyse the golf swing kinematics measured from inertial sensors to establish sensor parameters which could differentiate between skilled golfers and non-golfers (high handicap). It was found that the sensor data from the hand and upper arm were most discriminative of the two groups. Skilled golfers were able to consistently deliver high acceleration swings with lower pelvis movement compared to beginner golfers.